2002
DOI: 10.1097/00004872-200207000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Migraine is more frequent in individuals with optimal and normal blood pressure: a population-based study

Abstract: Our findings confirm that high blood pressure is not associated with the complaint of headache in the population. Individuals with migraine-like episodes of headache may have lower blood pressure than individuals without headache.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
79
4
6

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(103 citation statements)
references
References 22 publications
14
79
4
6
Order By: Relevance
“…6,37 It is commonly accepted that some symptoms, such as headache, are caused by high BP, which could be another reason for feeling ill after being aware of the diagnosis of hypertension. In population-based surveys and in the clinical setting, we and others have shown that there is no association between high BP and headache, 38,39 even for severe hypertension. 40 In addition, higher BP has been associated with lower perception of pain.…”
Section: Discussionmentioning
confidence: 65%
“…6,37 It is commonly accepted that some symptoms, such as headache, are caused by high BP, which could be another reason for feeling ill after being aware of the diagnosis of hypertension. In population-based surveys and in the clinical setting, we and others have shown that there is no association between high BP and headache, 38,39 even for severe hypertension. 40 In addition, higher BP has been associated with lower perception of pain.…”
Section: Discussionmentioning
confidence: 65%
“…Most of the studies that show an association between hypertension and migraine were done before the introduction of the International Headache Society (IHS) criteria in 1988. Recently Wiehe et al [15] and Lee et al [16] reported an association between low blood pressure and migraine. Again further and more detailed studies into this association will be very interesting.…”
Section: Discussionmentioning
confidence: 98%
“…Details of design and other results of this survey have been published. 4,[20][21][22][23] Participants were interviewed at home, using a pre-tested and structured questionnaire, which included evaluation of demographic characteristics and questions pertaining to education (years at school), alcoholic beverage consumption, physical activity at leisure time and other variables. Alcohol consumption was assessed by the pattern of consumption of alcoholic beverages (frequency-amount questions), classifying the participants as nondrinkers, social drinkers (1-29 g/day) or abusers (X30 g/day).…”
Section: Methodsmentioning
confidence: 99%